التطور الدلالي لمفهوم الألفاظ الحميرية واللهجات اليمانية القديمة في معاني القرآن الكريم/ Semantic development of the meaning of Himyarite words and the Ancient Yemeni dialects in the meanings of the Holy Quran - Hussein Al-Qahṭānī, Zaynah; Shehadeh Ali, Asem (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2019)
ملخص البحث: لقد خاض كثير من العلماء في خضم معركة الآراء التي دارت قديماً وحديثاً حول العلاقة بين العربية الشمالية واليمنية القديمة، ويأتي حكم أبي عمرو بن العلاء في مقدمة تلك الأحكام؛ فهو يرى أن الحميرية شيء والعربية شيء آخر، ومن قول أبي عمرو، وكان لهذا الحكم أثره الكبير في أفكار بعض علماء اللغة العربية القدامى وغيرهم ممن خاض في هذا الميدان؛ فاللغة اليمنية القديمة ليست لغة أعجمية، وليست هي نفسها عربية القرآن الفصحى المتوارثة بين الأجيال. تتبع الدراسة المنهج الوصفي والتحليلي، ويهدف البحث إلى استعراض أبرز المفردات الحميرية التي وردت في النقوش اليمانية ووردت ألفاظها ومعانيها في القرآن الكريم. توصلت الدراسة إلى ما يأتي: اندماج اللغة اليمنية في اللغة الحميرية وحملتها معها في ألفاظ القرآن الكريم، إن أبرز المفردات الحميرية التي وردت في النقوش اليمانية وردت ألفاظها ومعانيها في القرآن الكريم، إن أصول اللهجات اليمانية لها علاقة بالعربية الفصحى، وأن معاني المفردات في عامية أهل اليمن ودلالة الألفاظ الحميرية واللهجات اليمانية قد وردت في القرآن الكريم. الكلمات المفتاحية: التطور الدلالي-الألفاظ الحميرية-النقوش اليمانية-معاني المفردات. Abstract Many scholars have tried to contribute in the battle of views that have been going on traditionally and in modern time on the relation between the Northern Arabic and the ancient Yemeni dialect, and the opinion of Abu ʽAmru bin Al-ʽAlā' came at the top of those views. He saw that the Himyarite language and Arabic are two different entities, and this view had echoes in the thoughts of some traditional Arabic scholars and others who have been dwelling on this topic. Ancient Yemeni dialect is not a foreign dialect but at the same time is not the inherited Quranic Arabic as it is known. The study follows a descriptive analytical method and it aims to showcase the most prominent Himyarite words that were found in the Yemeni inscriptions and were also found in the Holy Quran. The study concluded with the followings; a merging took place between the Yemeni language and the Himyarite language and subsequently with the vocabularies of the Quran; that the meaning of the most prominent Himyarite words in the Yemeni inscriptions were also mentioned in the Holy Quran; that the origin of the Yemeni dialects was related to the Standard Arabic; that the meanings of the words of the dialect of Yemenis and the meaning of Himyarite words alongside with other Yemeni dialects have been mentioned in the Quran. Keywords: Semantic development – Himyarite vocabularies – Yemeni Inscriptions – Meanings of words Abstrak Sejumlah besar para cediakawan telah cuba untuk menyumbang dalam perdebatan pendapat yang telah berlarutan sekian lama sehinggalah ke zaman moden ini berkenaan dengan hubungkait antara loghat Arab utara dan loghat Yaman kuno serta pendapat Abu ‘Amru bin Al-‘AlÉ’ yang merupakan pendapat yang paling terkemuka di antaranya. Beliau berpendapat bahawa bahasa Himyar dan bahasa Arab adalah merupakan bahasa yang berbeza dan pendapat ini telah memberi kesan dalam pemikiran sebahagian ahli bahasa tradisional dan yang lain-lain yang membahaskan isu ini. Loghat kuno Yemen bukanlah satu dialek asing tetapi pada masa yang sama ia juga bukanlah bahasa warisan Al-Quran yang diketahui umum. Kajian ini mengikut pendekatan deskriptif analitikal dan bertujuan untuk mengetengahkan perkataan-perkataan Himyar yang penting yang ditemukan di batu-batu bersurat Yemen dan juga ditemukan di dalam Al-Quran. Kajian ini merumuskan perkara-perkara berikut: terjadi penggabungan antara bahasa Yemen dan Himyar dan seterusnya di antara perkataa-perkataan di dalam Al-Quran; maksud kebanuakan perkataan yang ditemukan dalam batu-batu bersurat itu juga turut disebut dalam Al-Quran; asal loghat-loghat Yemen ini juga mempunyai kaitan dengan Bahasa Arab Standard; terdapat di anatara maksud perkataan loghat Yemen and maksud perkataan-perkataan Himyar di samping loghat-loghat Yemen yang lain yang turut tersebut dalam Al-Quran. Kata kunci: Perkembangan semantik – Perkataan Himyar – Batu bersurat Yemen -Maksud perkataan